TINJAUAN BAHAN MATERIAL RAMAH ANAK DI RUANG PUBLIK KABUPATEN GROBOGAN SEBAGAI PENERAPAN KOTA LAYAK ANAK - hendarti, Lely; irnawan, dody (Jurnal Arsitektur dan Perencanaan (JUARA), 2019)
At the moment Grobogan Regency is in the midst of constructing a Green Park and Open Space. Grobogan Regency with its motto BERSEMI will beautify yourself besides being clean and green and shady. An informal playing environment, although not specifically designed, is also a concern for adult humans. Children can experience serious injuries while playing on the playground, which can occur in a variety of different ways. Causes of injury in children's playgrounds include falling, hit by moving equipment, running in balance equipment, sharp boundaries, bumps on the tool, pinched, hot equipment surfaces, and the collapse of game equipment. The main types of damage suffered by patients are fractures, bruises, blisters, sprains, and brain vinegar.However, whatever happened was a problem that occurred in Grobogan District. This research review is descriptive-qualitative. To provide comfort and safety to the playroom for children, it is done with the help of a questionnaire to the parents of visitors. The results obtained state that some materials in some children's games do not use standard materials.Â Â